Determinan Kepuasan Kerja Serta Dampaknya Terhadap Kinerja Pegawai Pada Kelurahan Di Kecamatan Pondok Aren Tangerang Selatan - Murdih, Murdih; Nuraeni, Nuraeni; Yusuf, M. (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
This study aims to determine the determinants of job satisfaction and its impact on employee performance at Kelurahan in Kecamatan Pondok Aren District, South Tangerang City. The research method used in this study is an associative method with a qualitative approach. The number of respondents to the study used was 75 ASN (Civil Affairs Apparatus) employees in Kelurahan in Pondok Aren District, South Tangerang City, with a sampling technique that is saturated samples because the entire population is taken as a whole. The results of the study were (a) leadership style has a positive and significant effect on employee job satisfaction, (b) organizational culture has a positive and significant effect on employee job satisfaction, (c) leadership style has an insignificant effect on employee performance, (d) organizational culture has an insignificant effect on employee performance, (e) job satisfaction has a positive and significant effect on employee performance, (f) leadership style has a positive and significant effect on employee performance on employee performance through job satisfaction, and (g) organizational culture has an insignificant effect on employee performance through job satisfaction.